2018
DOI: 10.1155/2018/7086059
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of an Oil-Soluble Polyethylene Wax Particles Temporary Plugging Agent

Abstract: In order to solve the problem of low strength, low permeability recovery rate, and narrow suitable temperature range of the oil-soluble temporary plugging agent, the idea of preparing the oil-soluble polyethylene wax particles temporary plugging agent (OPPTA) using polyethylene wax as the main raw material was proposed. Emulsifier and stabilizer were selected, and the dosage of emulsifier, stabilizer, and stirring speed was optimized. The method for preparing OPPTA was formed. The temporary plugging performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, deep formations contain a high proportion of hard, brittle rocks. If the plugging agent fails to effectively block the seepage channels in the formation, it is likely to cause wellbore instability and landslide, as well as drilling sticking and burial, which impedes the progress of drilling operations [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, deep formations contain a high proportion of hard, brittle rocks. If the plugging agent fails to effectively block the seepage channels in the formation, it is likely to cause wellbore instability and landslide, as well as drilling sticking and burial, which impedes the progress of drilling operations [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…10 At present, the common deformable particles in shielded temporary plugging drilling operations include softened particles such as acid-soluble fibers, 11 sulfonated asphalt, 12,13 and emulsified asphalt, 14 and deformable particles such as oilsoluble resin. 15 Kang et al 16 system containing 5.0% rigid granule, 3.0% fiber, and 2.5% elastic particle. Results showed that the reasonable combination of rigid granule, fiber, and elastic particle could create a synergy effect that makes the plugging stronger.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the common deformable particles in shielded temporary plugging drilling operations include softened particles such as acid-soluble fibers, sulfonated asphalt, , and emulsified asphalt, and deformable particles such as oil-soluble resin . Kang et al developed a temporary plugging system containing 5.0% rigid granule, 3.0% fiber, and 2.5% elastic particle.…”
Section: Introductionmentioning
confidence: 99%